Gli Irripetibili Anni'60 : Un dialogo tra Roma e Milano. - Aspesi, Natalia; Barbero, Luca Massimo; Bertolino, Giorgina; Codeluppi, Vanni; Dorfles, Gillo; Guadagnini, Walter; Pola, Francesca; Stolfi, Emanuele; Exhibition. Gli Irripetibili Anni'60 : Un dialogo tra Roma e Milano. Roma. Palazzo Cipolla Roma. Fondazione Roma. 2011-05-10. 2011-07-31 (Roma : Fondazione Roma Skira editore Genève - Milano, 2011)
Adami, Valerio ; Alviani, Getulio ; Anceschi, Giovanni ; Angeli, Franco ; Aricó, Rodolfo ; Arman ; Baj, Enrico ; Baruchello, Gianfranco ; Bello, Bruno Di ; Beuys, Joseph ; Blake, Peter ; Boetti, Alighiero ; Bonfanti, Arturo ; Boriani, Davide ; Burri, Alberto ; Calder, Alexander ; Castellani, Enrico ; Caulfield, Patrick ; Cavaliere, Alik ; César ; Hsiao-Chin ; Christo ; Ciussi, Carlo ; Colombo, Gianni ; Consagra, Pietro ; Crippa, Roberto ; Dadamaino ; Dias, Antonio ; Dorazio, Piero ; Dova, Gianni ; Duchamp, Marcel ; Fabro, Luciano ; Festa, Tano ; Fioroni, Giosetta ; Fontana, Lucio ; Hains, Raymond ; Hamilton, Richard ; Hockney, David ; Jones, Allan ; Klein, Yves ; Kline, Franz ; Kounellis, Jannis ; Lombardo, Sergio ; Man Ray ; Manzoni, Piero ; Mattiacci, Eliseo ; Mauri, Fabio ; Melotti, Fausto ; Mulas, Ugo ; Munari, Bruno ; Nangeroni, Carlo ; Nevelson, Louise ; Nigro, Mario ; Novelli, Gastone ; Paolini, Giulio ; Paolozzi, Eduardo ; Pardi, Gianfranco ; Pascali, Pino ; Persico, Paris Harold ; Pezzo, Lucio Del ; Pomodoro, Arnaldo ; Pomodoro, Gio ; Romagnoni, Bepi ; Rotella, Mimmo ; Savio, Francesco Lo ; Scanavino, Emilio ; Scheggi, Paolo ; Schifano, Mario ; Tacchi, Cesare ; Tadini, Emilio ; Tilson, Joe ; Uecker, Günther ; Uncini, Giuseppe ; de Vecchi, Gabriele ; Viani, Alberto ; Villeglé, Jacques ; Wiley, William T.
Italiaans
boek
Keywords: Italië; Milaan; Rome